2000
DOI: 10.1073/pnas.97.3.1062
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of terpenoids: YchB protein of Escherichia coli phosphorylates the 2-hydroxy group of 4-diphosphocytidyl-2C-methyl- d -erythritol

Abstract: A comparative analysis of all published complete genomes indicated that the putative orthologs of the unannotated ychB gene of Escherichia coli follow the distribution of the dxs, dxr, and ygbP genes, which have been shown to specify enzymes of the deoxyxylulose phosphate pathway of terpenoid biosynthesis, thus suggesting that the hypothetical YchB protein also is involved in that pathway. To test this hypothesis, the E. coli ychB gene was expressed in a homologous host. The recombinant protein was purified to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
172
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 206 publications
(176 citation statements)
references
References 21 publications
4
172
0
Order By: Relevance
“…These observations suggested that YgbB protein is involved in the deoxyxylulose phosphate pathway of terpenoid biosynthesis. This hypothesis was supported further by the fact that putative orthologs of dxr, dxs, ygbP, ychB, and ygbB are found in all completely sequenced genomes of microorganisms using the nonmevalonate pathway and are absent in all completely sequenced genomes of microorganisms using the mevalonate pathway with the exception of Pyrococcus horikoshii genome, which contains a putative ortholog of ygbP (15,16). The ygbB gene of E. coli was expressed in a recombinant E. coli host harboring the plasmid pQEygbB, which directs the synthesis of a modified YgbB protein with six consecutive histidine residues at the N terminus.…”
Section: Resultsmentioning
confidence: 54%
See 3 more Smart Citations
“…These observations suggested that YgbB protein is involved in the deoxyxylulose phosphate pathway of terpenoid biosynthesis. This hypothesis was supported further by the fact that putative orthologs of dxr, dxs, ygbP, ychB, and ygbB are found in all completely sequenced genomes of microorganisms using the nonmevalonate pathway and are absent in all completely sequenced genomes of microorganisms using the mevalonate pathway with the exception of Pyrococcus horikoshii genome, which contains a putative ortholog of ygbP (15,16). The ygbB gene of E. coli was expressed in a recombinant E. coli host harboring the plasmid pQEygbB, which directs the synthesis of a modified YgbB protein with six consecutive histidine residues at the N terminus.…”
Section: Resultsmentioning
confidence: 54%
“…§1734 solely to indicate this fact. A mixture containing 100 mM Tris hydrochloride (pH 8.0), 5 mM MgCl 2 , 5 mM ATP, 5 mM DTT, 2 Ci [2-14 C]4-diphosphocytidyl-2C-methylerythritol (117 Ci͞mmol), 5 mM 4-diphosphocytidyl-2C-methylerythritol labeled with 13 C as indicated, and 0.1 mg of recombinant YchB protein from E. coli (16) in a total volume of 4 ml was incubated at 37°C. The reaction was monitored by 31 P NMR.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…species), they are considered as functionally associated (Barker & Pagel, 2005;Bowers et al, 2004;Pellegrini et al, 1999). These methods applied to microorganisms and successfully discovered novel participants of known pathway (Carlson et al, 2004;Luttgen et al, 2000).…”
Section: Computational Prediction Methods For Ppismentioning
confidence: 99%